From consciousness to actions: shaping the library consciousness of ethnic minorities with an actor-network theory approach - Qian Quan; Wei Feng; Lihong Zhou (Information Research: An International Electronic Journal)
Introduction. Ethnic minorities (EMs) are a significant focus for public libraries striving to enhance more inclusive, egalitarian and sustainable services. Despite the availability of library services to EMs, their engagement in libraries is still relatively low, which can be further attributed to the lack of library consciousness.